Pelatihan Media Presentasi Berbasis Online Focusky : id - Ady Rukma; Djuanda; Muhzin Z; Samnur; Badaruddin Anwar (Program Studi Sarjana Terapan PTM FT UNM, 2024)
Students majoring in Mechanical Engineering Education as prospective educators are not yet familiar with Focusky online-based presentation media, even from initial observations there are students who are not yet proficient in operating computers. This problem is a basic reference for the need to carry out Focusky Online-based presentation media training in making presentations as a teacher so that they are interesting and not boring. Competencies of Mechanical Engineering Education students are prepared as teaching staff at the vocational school level. The curriculum structure contains courses on learning media and learning technology, so that this training becomes a trigger or socialization of the use of Focusky online-based presentation media, mastery of how to make presentations with Focusky. The aim of this training is mastery of adequate basic knowledge about online-based presentation media Focusky, increasing knowledge about online-based presentation media that is open source, Based on the results that have been achieved, then it can be concluded as follows:secara uMum partners in this IBM activity can master the training material, both theoretical knowledge about the theory of using Focusky Online-based presentation media and skills in making presentations with Focusky.Training participants can make a good and interesting Focusky Online-based presentation. The participants' participation and enthusiasm for this activity is very positive, as can be seen from their seriousness in following the training carried out.